2000
DOI: 10.1016/s0042-6989(00)00102-4
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent processing of saccades in visual search

Abstract: We provide evidence that the saccadic system can simultaneously program two saccades to different goals. We presented subjects with simple visual search displays in which they were required to make a saccade to an odd-colored target embedded in an array of distractors. When there was strong competition between target and distractor stimuli (due to color priming from previous trials), subjects were more likely to make a saccade to a distractor. Such error saccades were often followed, after a very short inter-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
198
0
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 226 publications
(223 citation statements)
references
References 48 publications
23
198
0
2
Order By: Relevance
“…4B, slope median ϭ Ϫ0.43, min ϭ Ϫ0.16, max ϭ Ϫ0.79, r 2 median ϭ 0.18, min ϭ 0.04, max ϭ 0.41, P Ͻ 0.02). These data replicate previous work (Becker and Jurgens 1979;McPeek et al 2000;Ray et al 2004), indicating that some aspect of the second corrective saccade was processed during the preparation of the first erroneous saccade itself.…”
Section: Parallel Programming During Error Correctionsupporting
confidence: 90%
See 1 more Smart Citation
“…4B, slope median ϭ Ϫ0.43, min ϭ Ϫ0.16, max ϭ Ϫ0.79, r 2 median ϭ 0.18, min ϭ 0.04, max ϭ 0.41, P Ͻ 0.02). These data replicate previous work (Becker and Jurgens 1979;McPeek et al 2000;Ray et al 2004), indicating that some aspect of the second corrective saccade was processed during the preparation of the first erroneous saccade itself.…”
Section: Parallel Programming During Error Correctionsupporting
confidence: 90%
“…More specifically, it is now well established that as the duration between the appearance of the second target and the beginning of the first saccade, which is the time available to the saccadic system to reprogram the second saccade (known as the reprocessing time), increases, the interval between the two saccades decreases and may even fall below the normal reaction time. Such a pattern of responses has led to the hypothesis that the corrective saccade may be programmed in parallel with the erroneous saccade (Becker and Jurgens 1979;McPeek et al 2000;Ray et al 2004). However, because saccade programming is composed of at least two stages, a visual stage that identifies the location of a target and a motor stage that prepares and executes the oculomotor command (Hooge and Erkelens 1996;Ludwig et al 2005; Thompson et al 1996;Viviani 1990), the extent to which parallel processing of correction may occur in anticipation of an error is still not clear in double-step tasks.…”
Section: Introductionmentioning
confidence: 99%
“…We used an adapted version of the double step paradigm (Becker and Jurgens 1979) with concurrent processing of two sequentially illuminated targets (at a 200 ms inter-stimulus interval) to observe the largest amount of primary and secondary eye movement (as in McPeek et al 2000). As shown in Fig.…”
Section: Figure 6 About Herementioning
confidence: 99%
“…The initial eye shift is a reflexive one that occurs with an average latency of approximately 200 ms (Pelisson et al 2010;Hu and Walker 2011). However, if a second light cue is presented at or around the time of response to the first, a secondary eye movement occurs resulting from an inhibition of the initial response and a re-orientation of the eye towards the new target (Gaymard et al 1998;McPeek et al 2000). The CNS controls this secondary eye shift based on an error signal created between the 'reflexive' saccade and a visual representation of the new target position (Tian et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Whereas saccadic trajectories in most studies, including the studies referred to above, deviate away from a distractor, it has been demonstrated that saccades may also deviate toward a location. For instance, saccadic deviation toward a distractor has been shown in visual search experiments in humans (Godijn and Theeuwes 2002;McPeek et al 2000;Walker et al 2006) and monkeys (McPeek et al 2003;McPeek and Keller 2001;Port and Wurtz 2003).…”
Section: Introductionmentioning
confidence: 99%